ANALISIS STRATEGI PEMASARAN DENGAN MENGGUNAKAN METODE SWOT TERHADAP KEPUASAN KONSUMEN (STUDI KASUSUD. FROTUNA BROWNIES KUKUS GRESIK) - Khadijah, Susan Novitasari (GEMA EKONOMI, 2019)
The purpose of this study is to identify the factors that most influence consumer satisfaction at UD. Fortuna Brownies Kukus Gresik is based on analysis from themarketing mix (Product, Price, Place and Promotion) to determine alternativemarketing strategies for gresik steamed brownies based on the SWOT analysis. Theresults of this study indicate that there is a relationship simultaneously Marketingmix has an effect on consumer satisfaction. Price variable as the dominant variableinfluencing consumer satisfaction. The results of the SWOT IFE (internal factorevaluation) and EFE (eksternal factor evaluation) matrix analysis show UD. FortunaBrownies Gresik steamer is in quadrant 1 which means that the strategy used is thestrategy of Strengths Opportunies (SO) or Growth strategy which shows that UD.Fortuna Brownies steamed Gresik belongs to a growing business and has a strongposition and opportunity. DOI 10.5281/zenodo.3629911